Geological Terrain Mapping using Geographic Information System (GIS) and Drone Photogrammetry - Abdul Kahar, Muhammad Afiq; Madun, Aziman; Hussin, Hamzah; Abu Talib, Khaidir; Wahab, Saiful Wazlan (Journal of Sustainable Underground Exploration, 2021)
The research area was conducted within the Bukit Persekutuan, Kuala Lumpur, and it was located at the latitude 3Â° 8’32.93"N and longitude 101Â°40’32.80"E. The researcher carried out geological terrain mapping to evaluate the research area in accordance with the geological terrain classification attributes of each thematic map produced, namely, Terrain map, slope gradient map, erosion, and instability map, as well as construction suitability map. The occurrence of landslide events within the research area becomes a major contributing factor to thoroughly conducting an investigation by field mapping and analysing using the Geographic Information System (GIS) technology. The application of Geographic Information System (GIS) and drone photogrammetry images play an essential role to analyze and processing the data, thus, generate the thematic maps. The research area indicates that about 79.11% of the overall area was not appreciable with erosion, 8.58% contribute to the erosion, 11.00% of recent general instability and 2.97% represent a landslide event. The suitability for development mapping illustrated Class I (23.40), Class II (36.37%), Class III (26.39%), and Class IV (15.50%) where it can be referred to the construction suitability classification system, the suitability for development was high in class I, moderate in class II, low in class III and not suitable in class IV.